2022
DOI: 10.22336/rjo.2022.9
|View full text |Cite
|
Sign up to set email alerts
|

Survey of patient satisfaction after bilateral cataract surgery

Abstract: This is an open-access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…These movements might vary for each eye operated upon induced by ocular discomfort and stress. Past studies indicate that the first operated eyes experience less ocular discomfort [ 15 ]. This could be due to diminished anxiety and heightened awareness of pain during subsequent procedures, making individuals more cognizant of discomfort [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These movements might vary for each eye operated upon induced by ocular discomfort and stress. Past studies indicate that the first operated eyes experience less ocular discomfort [ 15 ]. This could be due to diminished anxiety and heightened awareness of pain during subsequent procedures, making individuals more cognizant of discomfort [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additional to the physiological factors, the order of surgical operations might influence short-term microdistortions of the Bowman's layer post-SMILE surgery, potentially impacting short-term results [ 15 ]. We also speculate the anesthesia factors involved.…”
Section: Discussionmentioning
confidence: 99%
“…This finding agreed with Yotsukura et al, (2020) who reported that meeting patients' needs lead to better outcomes and improve patient's satisfaction. Moreover Kinga & Ursula, (2022) reported meeting patient expectation induce improvements in patients related practice, better achievement of needs, enhance the quality of care, convenience of care and improve health outcomes. Also agreed with (Ezenwa and Nwosu, 2020;Chawla andBenbadis, 2022 &Yotsukura, et al, 2020) who reported that meeting patients' needs and expectation induce better outcomes as improve patient's satisfaction and quality of sleep.…”
Section: Discussionmentioning
confidence: 99%